Vaso-occlusive crises and costs of sickle cell disease in patients with commercial, Medicaid, and Medicare insurance – the perspective of private and public payers. (1st November 2020) - Shah, Nirmish R.; Bhor, Menaka; Latremouille-Viau, Dominick; Kumar Sharma, Vikash; Puckrein, Gary A.; Gagnon-Sanschagrin, Patrick; Khare, Ankur; Kumar Singh, Mukesh; Serra, Elizabeth; Davidson, Mikhaïl; Xu, Liou; Guerin, Annie
Abstract: Aim: To characterize vaso-occlusive crises (VOCs) and describe healthcare costs among commercially-insured, Medicaid-insured, and Medicare-insured patients with sickle cell disease (SCD). Materials and methods: The IBM Truven Health MarketScan Commercial (2000–2018), Medicaid Analytic eXtract (2008–2014), and Medicare Research Identifiable Files (2012–2016) databases were used to identify patients with ≥2 SCD diagnoses. Study measures were evaluated during a 12-month follow-up period, stratified by annual number of VOCs (i.e. 0, 1, and ≥2). Results: Among 16, 092 commercially-insured patients (mean age = 36.7 years), 35.3% had 1+ VOCs. Mean annual total all-cause healthcare costs were $15, 747, $27, 194, and $64, 555 for patients with 0, 1, and 2+ VOCs, respectively. Total all-cause healthcare costs were mainly driven by inpatient (0 VOC = 31.0%, 1 VOC = 53.1%, 2+ VOCs = 65.4%) and SCD-related costs (0 VOC = 56.4%, 1 VOC = 78.4%, 2+ VOCs = 93.9%). Among 18, 287 Medicaid-insured patients (mean age = 28.5 years, fee-for-service = 50.2%), 63.9% had 1+ VOCs. Mean annual total all-cause healthcare costs were $16, 750, $29, 880, and $64, 566 for patients with 0, 1, and 2+ VOCs, respectively. Inpatient costs (0 VOC = 37.2%, 1 VOC = 64.3%, 2+ VOCs = 72.9%) and SCD-related costs (0 VOC = 60.9%, 1 VOC = 73.8%, 2+ VOCs = 92.2%) accounted for a significant proportion of total all-cause healthcare costs. Among 15, 431 Medicare-insured patients (mean age = 48.2 years), 55.1% had 1+ VOCs. Mean annual total all-cause healthcare costs were $21, 877, $29, 250, and $58, 308 for patients with 0, 1, and ≥2 VOCs, respectively. Total all-cause healthcare costs were mainly driven by inpatient (0 VOC = 47.9%, 1 VOC = 54.9%, 2+ VOCs = 67.5%) and SCD-related costs (0 VOC = 74.9%, 1 VOC = 84.4%, 2+ VOCs = 95.3%). Limitations: VOCs managed at home were not captured. Analyses were descriptive in an observational setting; thus, no causal relationships can be inferred. Conclusions: A high proportion of patients experienced VOCs across payers. Furthermore, inpatient and SCD-related costs accounted for a significant proportion of total all-cause healthcare costs, which increased with VOC frequency.